Penerapan Standar Akuntansi Pemerintahan, Sistem Pengendalian Internal dan Kualitas Pegawai Pada Kualitas Laporan Keuangan - Setiawan, I Made Hendra; Rasmini, Ni Ketut (E-Jurnal Akuntansi, 2021)
This research aims to determine the application of government accounting standards, internal control systems and quality of employees on the quality of financial statements. This research was conducted at Udayana University. The sample used was the staff of the finance department of Udayana University with a total of 31 respondents. Non-probability sampling is a method of determining the sample used, namely saturation sampling. The results of this study indicate the application of government accounting standards, internal control systems and employee quality affect the quality of financial statements. The variable implementation of government accounting standards, internal control systems and employee quality influences the quality of financial statements by 83.1 percent while 16.9 percent is influenced by other variables.   Keyword: Implementation Of Government Accounting Standards; Internal Control Systems; Quality Officers And Quality Of Financial Statements.